Perfil metabólico e desempenho de bezerros holandeses alimentados com diferentes quantidades de sucedâneo de leite e concentrado de diferentes granulometrias - Daniele Aparecida Miranda (2013)
To aim available the effects to five protocol food upon the metabolic profile and body weight gain were used thirty Holsteins calves fed: 4MFI - ration fine corn + 4 Liters of Milk replacer; 4MFLO steam flaked corn + 4 liters; 4MGR grits corn + 4 liters; 6MFI - fine corn + 6 liters; 6/4MFI fine corn + 6 liters until 30 days old and 4 liters until the weaned, that was held abruptly 60 days old. Biochemistry analyzer enzymes, metabolites, protein and minerals was conducted. Intake greater amount of milk replacer not harmed the ration intake and 6MFI had greater body weight gain than 4MFI and 6/4MFI. Body weight gain was resembling among groups to available the particle size, although flaked corn has triggered low pH rumenal. Fine corn and grits corn allowed better rumenal environment and greater pH. The lowest of milk replacer at 30 days for 6/4MFI triggered metabolic profile unstable. 4MGR showed greater early development liver, demonstrated by the values transaminases and albumin.